PHYSICAL EXERCISE REDUCES INSULIN HORMONE SECRETION AND INCREASES GLUCAGON HORMONE SECRETION: A SYSTEMATIC REVIEW - Wibawa, Junian Cahyanto; Fudin, Muhammad Soleh (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2024)
The purpose of this study is to investigate and quantify the impact of exercise on insulin and glucagon levels. Employing a systematic approach, this research delves into various journal databases including Embase, PubMed, Web of Science, and Scopus. Criteria for inclusion in this study encompass articles on physical activity, insulin, glucagon, their mechanisms, and publications from the past five years. Only articles from anonymous journals are considered for inclusion. A total of 12,380 articles were identified from Embase, Web of Science, PubMed, and Scopus databases. Approximately ten articles meeting the criteria for this systematic review were thoroughly examined and analyzed. The study adhered to the reporting guidelines outlined in the PRISMA checklist for Systematic and Meta-Analysis. Findings from this systematic review analysis reveal a decrease in insulin secretion and an increase in glucagon production following physical exercise. This is associated with enhanced insulin sensitivity and increased glucose absorption by glucagon post-exercise. Incorporating physical exercise into one's routine is recommended as a proactive measure to enhance insulin sensitivity, elevate glucagon levels, promote glucose synthesis, mitigate energy imbalances, and uphold overall health.